Colo-appendico- duodenal fistula: Rare presentation of extrapulmonary tuberculosis - David Eng Yeow Gan; Rohamini Sibin; Alvin Oliver Payus; Firdaus Hayati (John Wiley & Sons Ltd, 2021)
A colo-appendico- duodenal fistula is a rare occurrence that results from extrapulmonary tuberculosis (TB) complications, especially in the endemic region.